The changing American neighborhood : the meaning of place in the twenty-first century - Mallach, Alan; Swanstrom, Todd (Cornell University Press, 2023)
"This book explores the role and importance of neighborhoods in America today, the forces undermining them, and the challenges facing local actors seeking to build good neighborhoods. Synthesizing the literature on neighborhood change with original, interdisciplinary research, the book establishes the importance of history and context in understanding the compexities of neighborhood change"--